Rapid and sensitive detection of NGAL for the prediction of acute kidney injury via a polydopamine nanosphere/aptamer nanocomplex coupled with DNase I-assisted recycling amplification. Issue 10 (27th April 2020) - Hu, Yiting; Yu, Xie-an; Zhang, Ying; Zhang, Ran; Bai, Xuefei; Lu, Mi; Li, Jiwei; Gu, Lifei; Liu, Ji-Hua; Yu, Bo-Yang; Tian, Jiangwei
Abstract : A rapid and sensitive method for NGAL detection has been developed to predict acute kidney injury and evaluate the protective effect of drug on renal disease. Abstract : Early detection of acute kidney injury (AKI) is important, as early intervention and treatment can prevent further kidney injury and improve kidney health. Neutrophil gelatinase-associated lipocalin (NGAL) has emerged as the earliest and promising non-invasive biomarker of AKI in urine, and has been used as a new predictive biomarker of AKI in the bench-to-bedside journey. In this work, a nanocomplex composed of a polydopamine nanosphere (PDANS) and a fluorophore-labelled aptamer has been constructed for the detection of NGAL using a DNase I-assisted recycling amplification strategy. After the addition of NGAL, the fluorescence intensity increases linearly over the NGAL concentration range from 12.5 to 400 pg mL −1 . The limit of detection of this strategy is found to be 6.25 pg mL −1, which is almost 5 times lower than that of the method that does not involve DNase I. The process can be completed within 1 h, indicating a fast fluorescence response. Furthermore, the method using the nanocomplex coupled with DNase I has been successfully utilized for the detection of NGAL in the urine from cisplatin-induced AKI and five-sixths nephrectomized mice, demonstrating its promising ability for the early prediction of AKI. This method also demonstrates the protective effect of the Huangkui capsule on AKI, and provides an effective way to screen potentially protective drugs for renal disease.